If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + 7) = 0 Reorder the terms: 7(7 + 2x) = 0 (7 * 7 + 2x * 7) = 0 (49 + 14x) = 0 Solving 49 + 14x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + 14x = 0 + -49 Combine like terms: 49 + -49 = 0 0 + 14x = 0 + -49 14x = 0 + -49 Combine like terms: 0 + -49 = -49 14x = -49 Divide each side by '14'. x = -3.5 Simplifying x = -3.5
| 3p-2p+p= | | (a-2)/2=-1 | | 4(c-5)=12 | | 21=-3(1-2x)-6(x-5) | | 6r-r=20 | | -4x-5=-4x+13 | | 2(7x+1)= | | 17c-16c=7 | | 1x^3-12x+8=0 | | 2x^2+11x-63= | | 2x+3(2x-1)=25 | | 8.5y=-153 | | 0.88=5c+3c | | 17y=8y+81 | | 3x+-16=180 | | -8(-7p+1)=328 | | 800*5*x=250 | | 6x-9/7=10x | | 14-3w=4w | | 12x^2+15x+3= | | -2y=-4x-20 | | (Y+9)*(y+2)= | | 1.17x=4.68 | | 8=-b/6 | | 6(x+1)=-x+3(2x-2) | | (Y+9)(y+2)= | | 2/5h=16 | | 300-.8m=120 | | 250*5*x=800 | | 8(c-2)=8c-16 | | Y=4(x-3)(x-3)-64 | | 6.25w=100 |